2019
DOI: 10.1177/2393957519885513
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Digital Entrepreneurship Gap the Case of Returnee Entrepreneurs in Morocco

Abstract: Despite the growing rates of Internet penetration and inflows of returnee entrepreneurs (REs) from Silicon Valley, there are still few examples of successful digital entrepreneurship ventures from emerging markets reaching international markets. Positioning itself at the intersection of returnee entrepreneurship, digital entrepreneurship and internationalization, this article is based on the case studies of the REs starting up digital ventures in Morocco. The results show that Moroccan digital entrepreneurship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 86 publications
0
10
0
Order By: Relevance
“…A study on digital entrepreneurship has shown that the spread of start‐up mania in Silicon Valley affects emerging markets that are geographically remote from Mountain View in the United States. Analysis by Wentrup et al (2019) demonstrates the strong desire of the market for renewable energy in establishing local digital entrepreneurship in the context of an emerging market. Wentrup emphasised the importance of stimulating digital entrepreneurship in emerging markets to reduce the gap in digital entrepreneurship level compared to the leading developed markets, and thus highlighted the perspective of emerging markets in digital entrepreneurship research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on digital entrepreneurship has shown that the spread of start‐up mania in Silicon Valley affects emerging markets that are geographically remote from Mountain View in the United States. Analysis by Wentrup et al (2019) demonstrates the strong desire of the market for renewable energy in establishing local digital entrepreneurship in the context of an emerging market. Wentrup emphasised the importance of stimulating digital entrepreneurship in emerging markets to reduce the gap in digital entrepreneurship level compared to the leading developed markets, and thus highlighted the perspective of emerging markets in digital entrepreneurship research.…”
Section: Resultsmentioning
confidence: 99%
“…A study on digital entrepreneurship has shown that the spread of start-up mania in Silicon Valley affects emerging markets that are geographically remote from Mountain View in the United States. Analysis byWentrup et al (2019) demonstrates the strong desire of the market for renewable energy in establishing local digital entrepreneurship in the context of an emerging market.Wentrup emphasised the importance of stimulating digital entrepreneurship in emerging markets to reduce the gap in digital entrepreneurship level compared to the leading developed markets, and thus highlighted the perspective of emerging markets in digital entrepreneurship research.The article sheds light on the heterogeneity and complexity of the modern digital economy. It also reveals a paradox: despite the relatively high level of Internet penetration in developing countries and low entry barriers in terms of costs, digital entrepreneurship in such markets remains at low levels of development.…”
mentioning
confidence: 99%
“…While localized asset ownership and knowledge of local context remain relevant for the network governance mechanisms of international digital platforms and, hence, require a degree of local presence in a host country (Verbeke & Hutzschenreuter, 2021), this governance is further aided by technological control . Such a decrease in real human interactions can result in disembodied IB relations and digital mistrust, which, in turn, engenders lower commitment levels (Wentrup et al, 2020). Importantly, this disembodiment does not imply that online spaces and communities become neutral platforms for doing business, as they still cannot exist without some form of social order (Kobrin, 2001).…”
Section: Theoretical Background: Network Approach and The Internation...mentioning
confidence: 99%
“…Internationalization is theoretically defined in International Business (IB) theories as the growing participation in global markets. Foreign direct investment (FDI), joint ventures, initial public offers (IPOs), technology exchange, and exports are some of the ways this happens (Johanson & Vahlne, 1977, 1990Wentrup, Nakamura, & Ström, 2020;Zahoor, Al-Tabbaa, Khan, & Wood, 2020). As a result, it is a phenomenon involving a wide range of organizational categories, including small and medium enterprises (SMEs), multinational enterprises (MNEs), universities, technological centers, government agencies, and even civil society representatives.…”
Section: Introductionmentioning
confidence: 99%
“…Research on internationalization holds paramount importance due to its profound implications for the socioeconomic advancement of nations, contributing significantly to economic expansion and employment generation (Bradley, Durufle, Hellman & Wilson, 2019;Roig, Sun-Wang & Manfredi-Sánchez, 2020;Van Schijndel, 2019;Wentrup et al, 2020). Moreover, it stands as a pivotal domain within studies on innovation and entrepreneurship, while enterprises increasingly engage in global ventures to access new markets and foster innovative practices (Ferreira, Fernandes, & Veiga, 2023;Theodoraki & Catanzaro, 2021).…”
Section: Introductionmentioning
confidence: 99%